Faktor-Faktor Yang Mempengaruhi Minat Anggota Dalam Memanfaatkan Produk Pembiayaan Murabahah di KSPPS BMT Berkah Kabupaten Ciamis: Fadila Mardiani - Mardiani, Fadila (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2024)
Cooperatives based on the sharia system developed amidst the rise of thousands of conventional cooperatives, especially on the financing provided to members. Financing is often used for cooperative activities because it is always related to plans to obtain income. The increase in financing products has a positive impact on economic progress. Therefore, with the phenomenon of increasing financing at one of the BMTs in Ciamis district, namely KSPPS BMT BERKAH, there has been an increase in murabahah financing products. The aim of conducting this research is to find out what factors influence members' interest in murabahah financing products at KSPPS BMT BERKAH. This research is qualitative research, namely using primary data, namely data that has been obtained from the object under study. Primary data from this research is the main source obtained from interviews. Meanwhile, secondary data is data obtained through intermediaries and parties who already have the data. Secondary data from this research is from books and documents and other things related to the author's title. The results of this research state that the factors for the increase in murabahah financing products are because most members easily understand this murabahah financing product compared to other financing products and BMT makes it easy for customer members to apply, namely easy terms and relatively small margins.